Perceptions and Preferences of Indian Clinicians Towards Metoprolol–Am lodipine Fixed-Dose Combination Therapy in Hypertension Management: A Cross-Sectional Survey-Based Study (Academia Journal of Medicine, 2026)
Background:Hypertension remains a leading contributor to cardiovascular morbidity and mortality in India. Combination therapy using fixed-dose formulations like Metoprolol (a β-blocker) and Amlodipine (a calcium channel blocker) has gained attention for improved compliance and synergistic efficacy. However, clinician perspectives on such combinations remain underreported in Indian settings. Objective:To assess the perceptions, prescribing preferences, and clinical rationale of Indian medical professionals regarding the use of Metoprolol–Amlodipine fixed-dose combination (FDC) therapy in the management of hypertension.Methods:A descriptive, cross-sectional survey was conducted among 112 practicing clinicians using a structured questionnaire. The tool captured demographic details, prescribing patterns, therapeutic rationale, patient age-related choices, and perceived benefits or limitations of the Metoprolol–Amlodipine FDC.Results:The majority of respondents (78.6%) preferred the Metoprolol–Amlodipine combination over other antihypertensive FDCs, particularly in younger patients and those with coexisting anxiety or high sympathetic tone. Perceived advantages included effective BP control (86%), improved adherence (72%), and symptom relief. Logistic regression revealed significant associations between clinician age group, years of experience, and preference for the combination (p < 0.05).Conclusion:Indian clinicians show a strong preference for Metoprolol–Amlodipine FDC therapy, attributing it to enhanced therapeutic efficacy, tolerability, and patient compliance. These findings support the growing clinical utility of β-blocker–CCB combinations in routine hypertension management and underscore the need for updated guidelines reflecting real-world practices.
Keywords: Hypertension; Fixed-Dose Combination; Metoprolol; Amlodipine; Clinician Survey; Antihypertensive Therapy.